2018
DOI: 10.1016/j.ihj.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of chronic kidney disease on the survival of octogenarian patients submitted to percutaneous coronary intervention

Abstract: ObjectiveTo evaluate the impact of chronic kidney disease on the survival of patients – 80 years of age undergoing percutaneous coronary intervention (PCI) in the long term.Methods273 subjects who underwent PCI between January 2010 and January 2016 were divided into four categories: (1) stable angina (SA) and creatinine clearance – 30 (n = 24); (2) patients with SA and CrCl <30 (n = 70); (3) patients with acute coronary syndrome (ACS) and CrCl – 30 (n = 51); (4) patients with ACS and ICC <30 (n = 128). Mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Chronic kidney disease is more prevalent in older patients because of the progressive loss of kidney function with age [ 22 ]. Cardiorrenal syndrome can also play a role in the severity of kidney injury, which is associated with worse outcomes [ 23 , 24 ]. The Impacto de la fragiLidad y Otros síndromes GEriátricos en el manejo y pronóstico Vital del ancianO con Síndrome Coronario Agudo sin elevación de segmento ST (LONGEVO-SCA) registry studied consecutive patients aged 80 years and assesed the impact of renal function in outcomes such as mortality or readmissions and its relation to frailty status.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Chronic kidney disease is more prevalent in older patients because of the progressive loss of kidney function with age [ 22 ]. Cardiorrenal syndrome can also play a role in the severity of kidney injury, which is associated with worse outcomes [ 23 , 24 ]. The Impacto de la fragiLidad y Otros síndromes GEriátricos en el manejo y pronóstico Vital del ancianO con Síndrome Coronario Agudo sin elevación de segmento ST (LONGEVO-SCA) registry studied consecutive patients aged 80 years and assesed the impact of renal function in outcomes such as mortality or readmissions and its relation to frailty status.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…2 Age is one of the accepted criteria of how CHiP is defined, and is known to be an important predictor of worse PCI outcomes. 3 While there are no specific studies that have looked explicitly at CHiP outcomes according to age in the real-world setting, prior studies that have focused on individual CHiP components have suggested worse outcomes associated with older age in chronic renal failure (CRF), 4 PCI in chronic total occlusions (CTOs) 5,6 left main (LM) PCI, 7 or severe vascular calcification. 8 There have been no previous studies focused on whether the type of CHiP cases undertaken in different age groups varies by age, and whether the growth of CHiP and the types of cases undertaken has changed differentially among different age groups.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Age is one of the accepted criteria of how CHiP is defined, and is known to be an important predictor of worse PCI outcomes. 3 While there are no specific studies that have looked explicitly at CHiP outcomes according to age in the real‐world setting, prior studies that have focused on individual CHiP components have suggested worse outcomes associated with older age in chronic renal failure (CRF), 4 PCI in chronic total occlusions (CTOs) 5 , 6 left main (LM) PCI, 7 or severe vascular calcification. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Although no studies have directly examined CHiP outcomes according to age in the real-world setting, findings from studies focusing on specific CHiP types indicate poorer outcomes among older individuals. For instance, worst outcomes post-PCI were observed in those elderly patients with chronic renal failure 142 , those who underwent a CTO PCI 143,144 , those who received calcium modification therapy 145 , and those who underwent left main PCI 146 .…”
Section: Introductionmentioning
confidence: 99%